Implementation and Assessment of a Curriculum for Bedside Ultrasound Training. (1st May 2015) - Turner, Elizabeth E.; Fox, J. Christian; Rosen, Mark; Allen, Angela; Rosen, Sasha; Anderson, Craig
Abstract : Objectives: This study assessed a curriculum for bedside ultrasound (US) and compared outcomes from 2 common training pathways. Methods: The program consisted of e‐learning paired with expert‐led hands‐on training administered to pulmonary/critical care and cardiology fellows with no prior formal training in bedside US. This "simulation‐based learner" group completed a survey of attitudes and confidence before and after training, and knowledge and skills were assessed after training. The surveys and scores of the simulation‐based learners were compared to the scores of "experts, " who were US‐trained emergency physicians, and "apprentice learners, " who were intensivist physicians informally trained in bedside US on the job during fellowships. Results: There was a significant difference in the self‐reported level of prior training between the groups (simulation‐based learners, 2.8; apprentice learners, 3.7; experts, 4.1, on a scale of 1–5 [ P = .02]) but no difference in the interest level or perceived importance of bedside US. The study curriculum was successful, as shown by scores that exceeded the comparison groups in the cardiac and pulmonary courses (cardiac: simulation‐based learners, 80%; apprentice learners, 73%; experts, 62% [ P = .001]; pulmonary: 84%, 75%, and 72%, respectively [ P =.02]). The simulation‐based learners gained confidence in skills, whereas the comparison groups lost confidence after testing ( P < .005); however, the simulation‐based learners gained confidence in US subject areas that were not taught (abdomen [ P <.002] and miscellaneous [ P =.005]). Conclusions: The simulation‐based learner curriculum resulted in comparable or greater knowledge and confidence in each area of US versus the comparison groups. Findings of overgeneralization of confidence highlight the importance of quality assurance and supervision in bedside US training programs.